Flavor halos andconsumer perceptions offood healthfulness. (8th April 2019) - Pham, Nguyen; Morrin, Maureen; Bublitz, Melissa G.
Abstract : Purpose: This paper aims to examine how repeated exposure to health-related products that contain flavors (e.g. cherry-flavored cough syrup) create "flavor halos" that can bias perceptions about the healthfulness of foods that contain the same flavors (e.g. cherry-flavored cheesecake). Design/methodology/approach: Six experiments, using both between- and within-subjects designs, explore the effects of flavor halos in hypothetical and actual consumption settings. They test the underlying mechanism, rule out competing explanations and identify an opportunity to correct the cognitive biases created by flavor halos. Findings: Flavor halos can be created via repeated exposure to flavored medicinal products in the marketplace. These flavor halos bias dieters' judgments about the healthfulness of vice foods containing such flavors. Dieters are motivated toward a directional conclusion about food healthfulness to mediate the guilt associated with consuming indulgent products. Providing dieters with corrective information mitigates these effects. Research limitations/implications: The authors examine one way flavor halos are created –via repeated exposure to flavored medicinal products. Future research should explore other ways flavor halos are created and other ways to mitigate their effects. Practical implications: Considering the prevalence of obesity, organizations striving to help consumers pursue health goals (e.g. weight watchers) can use flavors to improve dietary compliance. Health-care organizations can help consumers understand and correct the cognitive biases associated with flavor halos. Originality/value: By identifying flavor halos, this work adds to the literature investigating how flavors influence consumers' judgments about healthfulness. The results suggest dieters apply flavor halos as they engage in motivated reasoning to license their indulgent desires.